Transfer Pricing and Multinational Enterprises - Bondarenko, Mariia; Brůna, Karel, 1973-; Šíma, Ondřej; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2018)
This thesis focuses on the tax concept of transfer pricing. The main purpose of the thesis is to investigate the nature of transfer pricing both from companies’ and tax authorities’ perspective, focusing on the transfer pricing methods available in context of the OECD Guidelines, with the following comparison of the differences between the frameworks established in different countries through the detailed analysis of local legislations. In order to achieve this goal the basic characteristics of the transfer pricing phenomenon are examined; the process of transfer pricing is explained and the following research of the legislations of selected countries is conducted.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses